Biomechanical Performance of Menisci under Cyclic Loads - J.-G. Tseng; B.-W. Huang; Y.-T. Chen; S.-J. Kuo; G.-W. Tseng (Applied Bionics and Biomechanics)
The meniscus, composed of fibrocartilage, is a very important part of the human knee joint that behaves like a buffer. Located in the middle of the femoral condyles and the tibial plateau, it is a necessary structure to maintain normal biomechanical properties of the knee. Whether walking or exercising, the meniscus plays a vital role to protect the articular surface of both the femoral condyles and the tibial plateau by absorbing the conveying shock from body weight. However, modern people often suffer from irreversible degeneration of joint tissue due to exercise-induced harm or aging. Therefore, understanding its dynamic characteristics will help to learn more about the actual state of motion and to avoid unnecessary injury. This study uses reverse engineering equipment, a 3D optical scanner, and a plastic teaching human body model to build the geometry of knee joint meniscus. Then, the finite element method (FEM) is employed to obtain the dynamic characteristics of the meniscus. The results show the natural frequencies, mode shapes, and fatigue life analysis of meniscus, with real human material parameters. The achieved results can be applied to do subsequent knee dynamic simulation analysis, to reduce the knee joint and lower external impacts, and to manufacture artificial meniscus through tissue engineering.